2018
DOI: 10.1111/are.13747
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on physiological energetics of a fast-growing selective strain and a hatchery population of the Pacific oyster (Crassostrea gigas )

Abstract: Growth is an important aquaculture trait, which has been one of the most important traits for genetic improvement in aquatic species. Numerous fast-growing domesticated aquaculture organisms are being cultured, but the physiological processes underlying growth remain largely unexplored. The Pacific oyster (Crassostrea gigas) is one of the most widely farmed bivalves. In order to improve the productivity traits, a fast-growing selective strain of C. gigas was established. In this study, we compared physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Physiological processes related to these mechanisms include clearance rate (CR), oxygen consumption rate (OCR), ammonia excretion rate (AER), and enzyme activities. Therefore, ingestion and energy metabolism of some commercial bivalve species have received considerable attention (Ibarrola et al, 2017;Zhang et al, 2018). Individuals might exhibit faster growth due to increased energy acquisition and maintenance or growth costs (Bayne et al, 1999;Meyer and Manahan, 2010;Tamayo et al, 2011), and this explanation is applicable for other bivalve larval stages (Pace et al, 2006;Tamayo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physiological processes related to these mechanisms include clearance rate (CR), oxygen consumption rate (OCR), ammonia excretion rate (AER), and enzyme activities. Therefore, ingestion and energy metabolism of some commercial bivalve species have received considerable attention (Ibarrola et al, 2017;Zhang et al, 2018). Individuals might exhibit faster growth due to increased energy acquisition and maintenance or growth costs (Bayne et al, 1999;Meyer and Manahan, 2010;Tamayo et al, 2011), and this explanation is applicable for other bivalve larval stages (Pace et al, 2006;Tamayo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These theories provide a feasible scheme for improving the growth characteristics of bivalves (Newkirk, 1980;Evans and Langdon, 2006;Schöne et al, 2021). Numerous studies have confirmed effective improvement in commercial traits of bivalve species through selective experiments (Deng et al, 2009b;Gu et al, 2011;Li et al, 2011;Zhang et al, 2018). Physiological differences between improved selected and non-selected groups were explored (Bayne et al, 1999;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological energetics analysis of the fast-growing oysters suggested that the selectively bred oysters had a higher energy gain than unselected oysters, while the basal metabolic rate between them was not significantly different. Therefore, fast-growing oysters possess superior energy budget for growth (Zhang et al, 2018). Gene-associated single nucleotide polymorphism (SNP) markers were developed for association analysis of the markers with growth traits, allowing identification of a number of SNP markers with allele frequencies showing a significant difference between fast-growing oysters and unselected commercial control oysters (Wang and Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, temperature and salinity also affect the metabolism of bivalves, and therefore change in these factors result in change in the growth rate of bivalves (e.g. Liu et al 2018;Zhang et al 2018;Sanders et al 2018;Haider et al 2019); for example, low water temperatures might reduce energy requirements, and as a result, less food would be required for growth; under high water temperature, the opposite phenomenon might be observed. So far, the biological effects of several environmental factors, such as ambient water temperature, salinity, and dissolved oxygen concentration, on F. mutica have been investigated in the laboratory (Nogami et al 1981;Tanimoto et al 2015).…”
Section: Discussionmentioning
confidence: 99%